KAPASITAS REGENERASI PADA AREAL BEKAS TEBANGAN DI IUPHHK PT. INHUTANI I, BERAU, KALIMANTAN TIMUR - , IDHAM GUFAN NAWANGGA ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Indonesian tropical forest implements silviculture system as the foundation for the sustainable forest management. One of the systems is Tebang Pilih Tanam Indonesia (TPTI). Especially in some commercial species, the information availability becomes important foundation for sustainable forest management guiding. This research is aim to: (1) structure, composition and the seedling, sapling, pole, and tree regeneration capacity, (2) commercial species standing stocks volume in various ages in logged over area. This research is attempts to Logged Over Area (LOA) in IUPHHK Inhutani I Ltd, UMH Meraâang, Kalimantan Timur. The method that used is an inventory of permanent sample plots 100 m x 100 m are structrured (nested sampling). The measured data includes the type, height, diametes breast height, high boles, 4 the width of the canopy, and widest canopy height. The analysis used is Importance Value Index, Variety Species Index, Type Richness Index, number regeneration distribution, and commercial species diameter in each different growth in young (5 years), medium (18 years), and old (29 years) LOA. Regeneration structure in LOA indicates the normal characteristic by formed âJâ reverse curve. The pole and tree regeneration composition are increase its number from the young into old LOA, whereas the volume is decrease. The decrease is caused by the illegal logging and the work behavior of Inhutani I Ltd that harvest timber tree commercial species. The regeneration composition of sapling and seedling level in average LOA is at the lowest number rather than the old and young LOA. In other hand, the dominant commercial species of old and young LOA trees is kind of Dipterocarpaceae (Shorea sp.), class, beside the young LOA is dominated by non commercial species such as nyatoh (Palaquium sp.). The variety species value in each level of all LOA can be categorized as average level (1,5 â 3,5). The capital species value of the average LOA is categorized in high level (R1 > 5,0) and average level (3,5 - 5,0) for both of young and old LOA.